Prediction Model of Shear Force Capacity and Stiffness of the Connections in Timber-to-Timber Composite structures - Hazri, Muhammad Hadi (Universiti Sains Malaysia, 2022)
This paper presents the findings of an extensive experimental study on the short-term mechanical performance of timber screw connections made from both softwood and hardwood species, using different types of fasteners (inserted at 45 and 90 degrees to the grain) and different types of timber products (solid sawn timber, glued laminated timber, cross laminated timber, and laminated veneer lumber). The test configurations were designed to mimic the connections found in timber-to-timber hybrid composite structures for usage in both new and retrofit projects. Eurocode 5 provides guidance for determining the shear force capacity of connections made of timber-to-timber composite structure. Furthermore, Multiple Linear Regression (MLR) analysis was used to predict the shear force capacity and stiffness model from a set of data from previous work. 39 specimens from push-out test were extracted to conduct the analysis. It was known that the density of timber influenced the shear force capacity and angle of screw influence the stiffness in the connection.